Dynamics of CD4+ T cell responses against Listeria monocytogenes - Graw, Frederik; Weber, K. Scott; Allen, Paul M.; Perelson, Alan S. (Journal of Immunology, 2012)
The generation of CD4+ T cell memory cells is poorly understood. Recently, two different murine CD4+ TCR transgenic T cell lines, LLO118 and LLO56, both specific for the same epitope but differing in their expression level of the cell surface protein CD5, were generated. Notably, these cell lines showed different behavior upon primary and secondary exposure to Listeria monocytogenes. Whereas LLO118 showed a stronger primary response and generated more robust CD8+ T cell help upon secondary exposure, LLO56 CD4+ T cells had a dramatically better recall response. Using different mathematical models, we analyzed the dynamics of the two CD4 + T cell lines in mice during infection with L. monocytogenes. Our models allowed the quantitative comparison of the two T cell lines and provided predictions for the conversion of naive T cells into memory cells. LLO118 CD4+ T cells are estimated to have a higher proliferation rate than LLO56 CD4+ T cells upon primary exposure. This difference can be explained by the lower expression level of CD5 on LLO118 CD4+ T cells. Furthermore, LLO56 memory cells are predicted to have a 3-fold longer half-life than LLO118 memory cells (t1/2LLO118 ≈ 4.3 to 5 d and t1/2LLO56 ≈ 11.5 to 13.9 d). Although both cell lines differ in their memory capabilities, our analysis indicates no difference in the rate at which memory cells are generated. Our results show that different CD5 expression levels influence the proliferation dynamics of activated naive CD4+ T cells while leaving the conversion rate of those cells into memory cells unaffected.
CRIS-Team Scopus Importer:2022-12-14